Clinical correlates of acute pulmonary events in children and adolescents with sickle cell disease1. (3rd May 2013) - Paul, Rabindra; Minniti, Caterina P.; Nouraie, Mehdi; Luchtman‐Jones, Lori; Campbell, Andrew; Rana, Sohail; Onyekwere, Onyinye; Darbari, Deepika S.; Ajayi, Olaid; Arteta, Manuel; Ensing, Gregory; Sable, Craig; et al.
Abstract: Objectives: We aimed to identify risk factors for acute pulmonary events in children and adolescents in the Pulmonary Hypertension and the Hypoxic Response in SCD (PUSH) study. Methods: Patients with hemoglobin SS ( n = 376) and other sickle cell genotypes ( n = 127) aged 3–20 yrs were studied at four centers in a cross‐sectional manner. A subgroup ( n = 293) was followed for a median of 21 months (range 9–35). Results: A patient‐reported history of one or more acute pulmonary events, either acute chest syndrome (ACS) or pneumonia, was obtained in 195 hemoglobin SS patients (52%) and 51 patients with other genotypes (40%). By logistic regression, history of acute pulmonary events was independently associated with patient‐reported history of asthma ( P < 0.0001), older age ( P = 0.001), >3 severe pain episodes in the preceding 12 months ( P = 0.002), higher tricuspid regurgitation velocity (TRV) ( P = 0.028), and higher white blood cell (WBC) count ( P = 0.043) among hemoglobin SS patients. History of acute pulmonary events was associated with >3 severe pain episodes ( P = 0.009) among patients with other genotypes. During follow‐up, 43 patients (15%) had at least one new ACS episode including 11 without a baseline history of acute pulmonary events. History of acute pulmonary events (odds ratio 5.0; P < 0.0001) and younger age (odds ratio 0.9; P = 0.007) were independently associated with developing a new episode during follow‐up. Conclusions: Asthma history, frequent pain, and higher values for TRV and WBC count were independently associated with history of acute pulmonary events in hemoglobin SS patients and frequent pain was associated in those with other genotypes. Measures to reduce pain episodes and control asthma may help to decrease the incidence of acute pulmonary events in SCD.